Fecal g. Streptococcus and g. Eubacterium_coprostanoligenes_group combined with sphingosine to modulate the serum dyslipidemia in high-fat diet mice. Issue 6 (June 2021) - Wei, Wei; Jiang, Wenbo; Tian, Zhen; Wu, Huanyu; Ning, Hua; Yan, Guangcan; Zhang, Ziwei; Li, Zixiang; Dong, Feng; Sun, Yongzhi; Li, Ying; Han, Tianshu; et al.
Summary: Background & aims: Although high-fat diet (HFD) could impact the composition of fecal microbiome and their metabolites, it is still largely unknown which fecal bacteria and metabolites are relatively important in responding to the HFD. This study aimed to identify the crucial fecal bacteria and metabolites in the HFD mice using a microbial-metabolite network, and to investigate the synergistic mediation effect of the crucial fecal bacteria and metabolites on serum dyslipidemia induced by the HFD. Methods: The 16srDNA sequencing and the ultra-performance liquid chromatography (UPLC/TOF MSMS) platform were performed to characterize the composition and function of fecal microbiome, and metabolites in the HFD. The microbial-metabolite network, correlation and mediation analyses were performed to examine the relationships among fecal microbiome, metabolites, and serum dyslipidemia indicators. Mice models were conducted to evaluate the effect of fecal metabolite on dyslipidemia. Results: Compared to the control, 32 genera were altered in the HFD, including 26 up-regulated and 6 down-regulated. A total of 42 altered pathways were observed between the control and HFD, and the "Glycosphingolipid biosynthesis" was identified as the most significant pathway (fold change = 0.64; p < 0.001). Meanwhile, 49 fecal metabolites were altered in the HFD, and the fecal microbiome was associated with the fecal metabolism (M2 = 0.776, p = 0.008). Based on the microbial-metabolite network, two major hub genera were screened (HUB1: g. Streptococcus, HUB2: g. Eubacterium_coprostanoligenes_group ), and one bacterial metabolite, sphingosine, was found in this study. Further, the HUB2 was positively associated with fecal sphingosine (r = 0.646, p = 0.001), and its downstream metabolic pathway, "Glycosphingolipid biosynthesis" pathway (r = 0.544, p = 0.009). The regulatory relationship between the HUB2 and sphingosine synergistically mediated the effect of HFD on TCHO (33.7%), HDL-C (37.3%), and bodyweight (36.7%). Besides, compared to the HFD, the HFD with sphingosine supplementation had lower bodyweight (35.12 ± 1.23 vs. 39.42 ± 1.25, p < 0.001), TG (0.44 ± 0.08 vs. 0.52 ± 0.05, p = 0.002), TCHO (3.81 ± 0.34 vs. 4.51 ± 0.38, p = 0.002), and LDL-c (0.82 ± 0.09 vs. 0.97 ± 0.15, p = 0.016). Conclusions: The g. Streptococcus and g. Eubacterium_coprostanoligenes are two hub genera in the fecal micro-ecosystem of the HFD, and the g. Eubacterium_coprostanoligenes mediates the effect of HFD on dyslipidemia through sphingosine. Sphingosine supplementation can improve dyslipidemia induced by HFD. Graphical abstract: Image 1 Highlights: The alteration of fecal metabolic profiling is regulated by fecal microbiome imbalance in the High-fat diet (HFD). Two key hub genera are screened based on the microbial-metabolite network in the High-fat diet (HFD). The hub genus and sphingosine had a synergistic mediation effect on improving the HFD-induced dyslipidemia. Sphingosine supplementation could reduce the dyslipidemia caused by HFD.